Artificial Intelligence as a Support for Arabic Language Learning in Higher Education with VOSviewer Analysis - Utzinger Morales; Vanella Lopez; Schittny Joanan; Hirsiger Julia (Journal International Inspire Education Technology, 2022)
The world is increasingly showing the progress of human resources in the field of science and technology, and the development of knowledge about this technology also continues to accelerate rapidly with the discovery of many features that have sprung up to be utilized according to human technological needs. Especially in the field of education, the development of technology-based features is also increasing, supported by technology-based learning systems. Newly emerging learning systems, such as an online machine-based intelligence apk that performs class teaching movements according to the connection provided by humans, this effort is a type of association in the interaction between robots and humans with correspondences that are linked between signals and movements. In this case, the robot provides an educational learning system with a discourse recognition process. The use of robots in learning Arabic in higher education also shows how an educational institution designs the latest technology-based learning system with the use of online robots to assist the learning process in the classroom. This online robot learning system is closely related to the use of supporting wireless network cables in the online robot association; therefore, a bibliometric analysis will be carried out on the use of artificial intelligence in supporting Arabic language learning in higher education with the help of VOSviewer. The results of the VOSviewer overview will provide conclusions about the extent to which artificial intelligence effectively supports Arabic language learning in higher education.